A new species of Eusphalerum Kraatz, 1857 from the Eocene Baltic amber (Coleoptera, Staphylinidae, Omaliinae) - Shavrin, Alexey V.; Kairišs, Kristaps (Zootaxa, 2021)
A new species of the genus Eusphalerum Kraatz, 1857 (Omaliinae) from the Eocene Baltic amber is described and illustrated: Eu. bukejsi Shavrin, sp.n. The specimen was studied using X-ray micro-computed tomography (μCT), to obtain images of the habitus, body parts and aedeagus. Based on the shape of the aedeagus, it was compared with East Asian species of pollens and japonicum groups.